(untitled) (Journal of educational development exploration, 2026)
This article takes the core metaphor of "library is pharmacy, bibliography is prescription" as the entry point and systematically explores the innovative paths for public libraries and librarians to expand their social and emotional support functions under the background of the national reading and Healthy China strategy. The research first analyzed the conceptual connotation of "reading healing", traced its possible theoretical evolution from individual spontaneous behavior to library professional services, and based on the cross-perspective of library science, psychology, and narrative medicine, demonstrated the rationality and contemporary necessity of regarding libraries as "social and emotional pharmacies" and elevating librarians’ reading guidance services to "reading prescriptions". The core research focuses on the possibility of librarians playing the role of "reading healers", analyzing their intrinsic advantages (such as resource hubs, trust Spaces, and humanistic traditions) and extrinsic needs (gaps in social psychological services). Furthermore, through literature analysis and comparative studies, the research initially constructed the qualification framework that a "reading healer" should possess, covering four dimensions: professional knowledge, core skills, personal traits, and ethical boundaries, and presented it specifically through a detailed "three-level ability index system" table. Finally, this paper proposes a hierarchical, collaborative and continuous training path, including the embedding of professional education courses in library and information science, systematic training for in-service librarians, the establishment of interdisciplinary cooperative communities, and evidence-based evaluation and iteration of practical projects. The article also objectively analyzes the challenges faced by role promotion, such as blurred professional boundaries, librarians’ ability anxiety, and difficulties in effectiveness evaluation, and puts forward corresponding countermeasures. This study aims to provide theoretical references and practical blueprints for the transformation of library services, promoting the evolution of libraries from information service centers to "social healing Spaces" that enhance public mental health and overall well-being.